2021
DOI: 10.1021/acs.iecr.0c05294
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous MEA/PEG200 Absorbent with High Efficiency and Low Energy Consumption for CO2 Capture

Abstract: CO 2 capture by stripping with aqueous amine is a well-understood and widely employed technology. However, there still exist several drawbacks in the practical applications, such as high energy consumption and serious equipment corrosion. In this paper, an organic monoethanolamine/poly(ethylene glycol) 200 (MEA/PEG200) absorbent with low specific heat capacity, low vapor pressure, and a high boiling point was developed to substitute the aqueous amine systems. The absorption rate and capacity, the desorption ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…When the concentration of water in the system increases (the salt concentration decreases), some unexpected products may be produced, such as bicarbonate or little tricarbonate. These unexpected products may lead to boundary errors in the system. , The outlier systems, Nos. 85 and 89 , are abnormal at a low concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the concentration of water in the system increases (the salt concentration decreases), some unexpected products may be produced, such as bicarbonate or little tricarbonate. These unexpected products may lead to boundary errors in the system. , The outlier systems, Nos. 85 and 89 , are abnormal at a low concentration.…”
Section: Resultsmentioning
confidence: 99%
“…These unexpected products may lead to boundary errors in the system. 24,40 The outlier systems, Nos. 85 and 89, are abnormal at a low concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al 18 . and Tian et al 19 . studied the performance of 20 wt% [DETAH]Br and 0.5–5.0 M MEA in PEG200, respectively, indicating that nonaqueous absorbent has lower regeneration temperature and excellent corrosion‐resistance.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 For example, Bougie et al 17 studied the nonaqueous MEA solutions (20-70 wt%) in a mixture of ethylene glycol and 1-propanol (EG/PrOH), diethylene glycol monoethyl ether (DEGMEE), and N-methylformamide (NMF), and the 20 wt% MEA/DEGMEE solutions resulted in good CO 2 cyclic capacities and the lowest energy consumption, which was 78% lower than the traditional 30 wt% MEA aqueous solution. Chen et al 18 and Tian et al 19 studied the performance of 20 wt% [DETAH]Br and 0.5-5.0 M MEA in PEG200, respectively, indicating that nonaqueous absorbent has lower regeneration temperature and excellent corrosion-resistance. Furthermore, many studies on phase-change absorbents have been reported.…”
mentioning
confidence: 99%
“…Water-lean absorbents have emerged in response to the calling for substantial improvement of the aqueous approaches, which could render a viable method to circumvent the high parasitic energy loading because of their relatively lower heat of absorption as well as reduced reversal temperature. , Given the absence of the mass water diluent, equipment corrosion would also be relieved, along with enhancement of gravimetric capacity. To date, a variety of liquid absorbents that could operate under the nonaqueous condition have been devised and applied to CO 2 capture in the bench scale, examples of which are ionic liquids, deep eutectic solvents, siloxylated- and silylamines, alkanolguanidines, single-component amines, and their organic solutions. These absorbents would sustain in the liquid state before and after incorporation of CO 2 and could be thermally regenerated with fast kinetics at mild temperatures rather than at temperatures of 120 °C or above in the case of aqueous alkanolamines. Nevertheless, the industrial application of water-lean systems still has an intrinsic drawback to overcome, that is, the exponential increase of operating viscosity along with CO 2 uptake, which is usually several orders of magnitude larger than that of 30 wt % MEA solution and results in both inefficient internal mass transfer (deterioration of absorption and regeneration) and poor transportation in pipeline networks.…”
Section: Introductionmentioning
confidence: 99%